Adsorption of Bisphenol A on Peanut Shell Biochars: The Effects of Surfactants. (16th December 2019) - Wang, Fang; Zeng, Qiang; Su, Wenting; Zhang, Min; Hou, Lei; Wang, Zhong-Liang
Abstract : Bisphenol A (BPA) is a typical endocrine-disrupting chemical. The removal of BPA has raised much concerns in recent years. This paper examined the adsorption behavior of BPA to biochars and the different effects of cationic, anionic, and nonionic surfactants. The results indicated that peanut shell biochars prepared at 300°C (BC300), 500°C (BC500), and 700°C (BC700) showed strong adsorption affinity for BPA, and the adsorption affinity of biochars increased with the increase of pyrolysis temperature. The range of log K d values was 2.83∼3.71, 2.91∼4.57, and 3.24∼5.50 for BC300, BC500, and BC700, respectively. Both the type of surfactants and the properties of biochars could affect the adsorption behavior of BPA. Cetyltrimethyl ammonium bromide (CTAB) showed negligible effect on the adsorption of BPA on BC300, and the inhibition effect of CTAB was stronger with the increase of biochar pyrolysis temperature. Tween 20 and sodium dodecyl benzene sulfonate (SDBS) showed stronger inhibition effect than CTAB, especially on BC300. This is likely because the inhibition effect caused by competition of CTAB may be counterbalanced by the enhancement caused by the partitioning effect by adsorbed CTAB and the bridge effect between the –NH4 + group of CTAB and the phenol group on BPA/O-functional groups of biochars, whereas Tween 20 and SDBS do not have this bridge effect advantage. This study could provide insightful information for the application of biochars in removal of BPA.